Learning design for couple prenatal education program; birthing class - Ni Made Dwi Purnamayanti; I Gusti Agung Ayu Novya Dewi (Alma Ata University Press, 2023)
Background: The involvement of birth attendants has been shown to have a positive impact on pregnancy outcomes. Unprepared fathers tend to have negative experiences during childbirth. Mothers and partners need to be prepared since pregnancy to face childbirth and have a satisfying birth experience. It is necessary to arrange a learning program for childbirth classes not only for pregnant woman but also their partners.Objectives: The purpose of this study is to develop a birthing class learning design for the prenatal couple education program.Methods: This research design is research and development (R&D) level 1. The product to be developed is a birthing class learning design for prenatal couple education program. The stages of the research are 1) analysis of gaps and needs of the developed program; 2) Drafting; 3) internal validation of the design Results: This study found that the needs of mother and their partners for birthing classes are high. The material most needed in birthing class is husband’s role in delivery process. In the management of birthing class, mother and partner want a balance practicum and theory method, the duration of the class is 90 minutes, with the number of participants less than 5 couples and the use of learning modules. The birthing class learning design for prenatal couple education program is structured in form of training program curriculum that consist 1) competencies; 2) learning outcome; 3)study materials; 4) training subjects; 5) training course loads; 6) learning methods and 7) assessments. Conclusions The birthing class learning design for prenatal couple education program is needed by pregnant women and their partners. The design can be used for preparing the birthing class model.